Perfil de automedicação em duas populações do município de Teresina - Mendes, Cíntia Maria de Melo (2010)
The selfmedication refers to a common practice, and therefore concerning, among the Brazilians. It causes several consequences such as side effects, intoxications, delay and slowness for the diagnoses and treatments, besides the feared increase of bacterial resistance to the antimicrobial agents. OBJECTIVES:To analyze the practice of selfmedication in two samples of the population of Teresina that possesses distinct demographic and socioeconomic characteristics. Furthermore, to approach aspects of the pharmacoepidemiology and of the study in medication’s use. METHODOLOGY: Transverse study of population base that evaluated the self medication in two areas of Teresina, divided in: Group 01 with residents interviewed in Planalto Uruguai neighborhood – predomination of social classes C and D. Group 02 residents interviewed in Jóquei Clube neighborhood – predomination of social classes A and B. It was used a reminding period of 15 days for the medication’s use. The sample was acquired through a lottery of streets in each neighborhood and houses in each street. In the residencies assorted, were interviewed all the inhabitants that accepted to participate in the study. RESULTS: It was verified that the general consumption of medications, in both groups, is more frequent between women (67,8% group 01 and 55,8% group 02). As the ageism trate and auto medication, this study is according to the national literature that shows the gap between 20 and 50 years of age being the most practicing in auto medication in Brasil, independently of the gender. Among those that practiced auto medication, in group 01, 26,2% possess health insurance and in group 02, 65,2%. The increase of schooling, of the intervieweds, in both groups, contributes to the rise of selfmedication. The per capita income in group 01 with predominance of auto medication is until 0,5 minimum wage (52,4%) and for group 02 is from 1.6 minimum wage (64,1%). The selfmedication occurs, in majority, between one pharmaceutics’ specialty, in both groups. In both groups, the most frequent pharmacologic class is of the analgesics, followed by the anti-inflammatories( both groups) and the main motivation is pain complaints. CONCLUSION: This research showed interesting nuances of the selfmedication. Some suffers socio-demographic influences and others are independent of these factors. In general lines, it was possible to observe how common and trivial is the act of auto medication diffused in the population, following cultural patterns and aspects subtly influenced by socio-demographic conditions.